Avaliação do pH das secreções em hipofaringe, durante laparoscopia ginecológica: é seguro o emprego da máscara laríngea? - Lemos, Jeconias Neiva [UNESP] (2014)
Introduction: Although controversial, the laryngeal mask is now widely used for laparoscopies. In gynecological laparoscopy, in particular, there is an increase in the intra-abdominal pressure associated with the head-down position used during the procedure and an increase in the potential risk factors for the regurgitation of gastric contents with the potential to compromise the airways, and therefore, the occurrence of such phenomena during gynecological laparoscopy needs to be evaluated. Objectives - To evaluate the safety of using a ProSeal laryngeal mask airway (LMA-P) during gynecological laparoscopy, assessing the risk of regurgitation of gastric contents by measuring the pH of secretions in the hypopharynx during the anesthetic/surgical procedure. Methods - In total, 80 patients were evaluated who were under general anesthesia for gynecological laparoscopy in which airway access was maintained using a ProSeal laryngeal mask airway. Secretions in the hypopharynx were collected by aspiration using an esophageal drainage tube to measure their pH at various times during the anesthetic/surgical procedure. We used pH test strips, pH 2-9 (Merck, Darmstadt, Germany), and in case of any doubts, a pH meter was also used. A pH of ≤ 4.0 was considered positive for the regurgitation of gastric contents. Results - None of the pH measurements of analyzed secretions in the hypopharynx had a pH of ≤ 4.0. The mean pH of the secretions varied from 6.34 for the lower means to 6.50 for the higher means when measured at different time points, which are comparable to the normal pH of saliva. Conclusion - From these results, we conclude that the ProSeal laryngeal mask airway is a safe alternative for anesthesia during laparoscopic surgery for patients without risk factors for the regurgitation of gastric contents